PENGARUH KOMPOSISI PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI PAGODA ( Brassica narinosa L. ) - Badih Badih; Sugiyanto Saleh; Fetty Dwi Rahmayanti (Fakultas Pertanian Universitas Borobudur, 2021)
ABSTRACTResearch to determine the response of the Pagoda Mustard (Brassica narinosa L.)plant was carried out at the Experimental Garden of the Faculty of Agriculture, University of Borobudur, Campus A, Kalimalang Road, No.1. East Jakarta, fromDecember 2020 to February 2021. This study used a Monofactorial Design in aRandomized Block Design (RBD) with three (3) replications. The treatments testedconsisted of Red Soilwith Husk Charcoal (1:1), Red Soil with Compost (1:1), Red Soilwith Goat Manure (1:1), Red Soil with Chicken Manure (1:1). Three (3) samples wereassigned to each trial unit.The data were analyzed descriptively and inference consisting of the F test andfurther tests on five (5) parameters, namely, Plant Height, Number of Leaves, LeafArea, Wet Weight and Dry Weight. Data analysis used the Least Significance Different(LSD) Test at 5% real difference, using SPSS software version 24.The results of the analysis showed that the effect of the composition of the plantingmedium of Tanah Merah combined with husk charcoal (1:1) had no significant effect onthe growth of Pagoda Mustard (Brassica narinosa L.). The composition of the plantingmedia of Tanah Merah combined with compost (1:1) had a significant (significant)effect on the growth of Pagoda Sawi (Brassica narinosa L.). The composition of theplanting media combination of Tanah Merah with Goat Manure (1:1) did notsignificantly affect the Pagoda Mustard (Brassica narinosa L.) plant. The compositionof the planting media combination of Tanah Merah with Chicken Manure (1:1) was notsignificantly different to no significant effect on Pagoda Sawi (Brassica narinosa L.).Keywords: organic fertilizer, pagoda mustard (Brassica narinosa L.), red soil